Evaluation of flexible endoscope steering using haptic guidance - Reilink, Rob; Stramigioli, Stefano; Kappers, Astrid M.L.; Misra, Sarthak (The international journal of medical robotics + computer assisted surgery, 2011)
Background Steering the tip of a flexible endoscope relies on the physician's dexterity and experience. For complex flexible endoscopes, conventional controls may be inadequate. Methods A steering method based on a multi‐degree‐of‐freedom haptic device is presented. Haptic cues are generated based on the endoscopic images. The method is compared against steering using the same haptic device without haptic cues, and against conventional steering. Human‐subject studies were conducted in which 12 students and 6 expert gastroenterologists participated. Results Experts are significantly faster when using the conventional method compared with using the haptic device, either with or without haptic cues. However, it is expected that the performance of the subjects with the haptic device will increase with experience. Conclusions Using a haptic device may be a viable alternative to the conventional method for the control of complex flexible endoscopes. The results suggest that the use of haptic cues may reduce the patient discomfort. Copyright © 2011 John Wiley & Sons, Ltd.